Mental Health Burden in Higher Education: Exploring the Impact of Bullying, Social Support, and Happiness on Psychological Distress and Suicidal Ideation in Pakistani Students - Siyal, Fahad Jibran; Mahar, Muiz-U-Din; Memon, Khushboo Sarwar; Sheikh, Adeel Ahmed; Sheikh, Iqra Nawaz; Das, Dial; Chahwan, Adnan Ali; Jiskani, Shahzad Ali; Dodani, Amar; Tunio, Fatima; Lund, Nadeem; Shaikh, Bakhtawer; et al. (Indus Journal of Bioscience Research, 2025)
Background: University students face increasing psychological pressure due to academic demands, social changes, and limited mental health support – particularly in low-resource settings like Pakistan. Mental health disorders, suicidal ideation, and bullying are interlinked concerns with significant implications for student well-being, yet are underexplored collectively in the Pakistani context. Objective: To assess the prevalence of depression, anxiety, stress, and suicidal ideation among university students, and to evaluate the association of these outcomes with bullying, subjective happiness, and perceived social support. Methodology: A cross-sectional study was conducted at SMMBMU, Larkana from October to December 2024. A stratified random sample of 372 valid responses analyzed. Data were collected using a self-administered online questionnaire including DASS, SHS, and the F-SozU Social Support Scale. Statistical analyses were performed using SPSS v.24.0. A p-value of <0.05 was considered as statistically significant. Results: Psychological distress was prevalence across sample, with no significant differences observed by gender (p=0.887) or age group (p=0.526). Strong inverse correlations were found between psychological distress and both subjective happiness (r = -0.85, p<0.001) and social support (r= - 0.68, p<0.001). Regression analysis identified low happiness (β = -0.817) and low social support (β = -0.909) as significant predictors of distress (p<0.001). Bullying emerged as a major factor: bullied students had significantly higher scores for depression, anxiety, and stress, and were more likely to report suicidal ideation (p<0.001), low happiness, and poor social support. Conclusion: The study highlights a high burden of psychological distress among university students, with bullying, low happiness, and inadequate social support as major contributing factors. The findings underscore the urgent need for institutional mental health frameworks, anti-bullying policies, and psychosocial support systems within higher education settings. Culturally sensitive interventions are essential to reduce stigma and promote mental well-being.